Single cell sequencing deciphering the heterogeneous landscape of blastic plasmacytoid dendritic cell neoplasm with novel MYB-ZFAT fusion gene - Ruijuan Li; Wenyong Kuang; Haixia Yang; Benshan Zhang; Kexin Zhao; Weiyi Fang; Zhao Cheng; Xianming Fu; Hongling Peng (Cancer Cell International)
Abstract Background Blastic plasmacytoid dendritic cell neoplasm (BPDCN) is a rare, aggressive blood cancer from plasmacytoid dendritic cell precursors. It’s marked by CD4, CD56, CD123, and CD303/CD304 expression and involves molecular disruptions like chromatin deletions, mutations, and chromosomal translocations. Methods The current study employed a comprehensive method with clinical samples, histology, FACS immunophenotyping, karyotype analysis, transcriptome and protein structure analysis, and single-cell sequencing to explore BPDCN’s molecular basis. Results The study discovered a new MYB-ZFAT gene fusion in a BPDCN patient and showed a diverse cell population, contradicting a single cell type theory. It found four major clusters (Cluster 1,2,3,8 ) and one cluster (clulster 12) with unique profiles and roles in disease progression. The research noted Key pathways include T cell receptor signaling, NK cell cytotoxicity, and hematopoiesis are involved in pathogenesis. The study emphasized MYB activation’s role in BPDCN’s cellular clustering and identity. Conclusion The study indicates BPDCN’s complexity with varied cellular origins and a significant role for MYB activation in its development. This research deepens our comprehension of BPDCN’s pathogenesis and cell populations.